Russia’s North Pacific (Heidelberg University Publishing (heiUP), 2023)
"The series “Russia and the Asia-Pacific” explores political, economic, social, cultural and environmental interactions of the Russian Far East within its Asian-Pacific context as well as with the Russian capital in the past and present. Its first volume addresses from a multidisciplinary perspective notably the following questions: How were and are directives from a centre thousands of kilometers away perceived and implemented by actors in this region? To which extent was and is the centre successful or how did or does it fail in integrating a region as far away from the centre as the Russian Far East in its state structures? How have notions of “centre” and “periphery” changed over time?